ADHD, Lifestyles and Comorbidities: A Call for an Holistic Perspective – from Medical to Societal Intervening Factors - Weissenberger, Simon; Ptacek, Radek; Klicperova-Baker, Martina; Erman, Andreja; Schonova, Katerina; Raboch, Jiri; Goetz, Michal (Frontiers in Psychology, 2017)
The review examines Attention Deficit Hyperactivity Disorder (ADHD in its Child and Adult form) and its various presentations (Hyperactive Impulsive, Inattentive, and Combined) with a particular focus on environmental (incl. social factors), lifestyles and comorbidities. It is argued that ADHD is best understood in a holistic and interactive context and a vast empirical literature is presented to illustrate the point: Environmental factors include stress in general as well as exposure to toxins (phthalates, bisphenol A). Social factors are illustrated by effects of social deprivation and seduction to unhealthy lifestyles. Maternal lifestyle during pregnancy is pointed out (particularly her exposure to nicotine, alcohol, caffeine, and drugs, even seemingly benign medications like acetaminophen), which all tend to be related to ADHD. Family environment is discussed with respect to protective effect of (mainly authoritative and autocratic) parenting styles. Societal factors include mainly economic and political issues: income inequality and poverty (low SES is an ADHD risk factor) and a growing moral dilemma between a humanistic effort to globally spread the knowledge of ADHD and the medicalization and commercialization of the disorder. The second part of the review is devoted to ADHD related lifestyles and resulting comorbidities (e.g., food addiction and obesity, substance abuse, electronic media dependencies and conduct and personality disorders). Although ADHD is a neurodevelopmental disorder, its assessment and treatment are also linked to environmental, behavioral and social factors and their interactions.